The impact of social phobia on willingness to communicate in a second language: The mediation effect of ideal L2 self - Zhang, Chen; Zhang, Wenzhong (Frontiers in Psychology, 2022)
In recent years, a greater focus has been placed on the influential power of domain-general psychological properties in second language acquisition and learning. The investigations of these properties, such as grit, academic procrastination and enjoyment etc. have been extensively conducted and are well-documented. Notwithstanding the surge of academic inquiry, the link between psychopathological notions and second language learning has not been adequately established and thoroughly scrutinized. The current study, therefore, aims to broaden the spectrum of second language research and explore the impact of social phobia on willingness to communicate in the second language context. Meanwhile, this research introduces the self construct, particularly the ideal L2 self to further examine and elucidate the impact. 173 qualified Chinese speakers of L2 English participated in the study. By conducting correlation analysis, regression analysis and structural equation modelling analysis, it was revealed that social phobia had a significant negative impact on L2 willingness to communicate in social situations of meetings and public speaking. Ideal L2 self acted as a complete mediating role in the impact. Pedagogical implications and future directions were proposed and discussed.